The effect of aqueous extracts of Anethum graveolens L. on amygdala kindled in rats (Institue of Medicinal Plants, ACECR, 2018)
Background: Electrical kindling model is common models to create epilepsy of temporal lobe. Although hydro-alcoholic extracts of Anethum graveolens L. had Anticonvulsants effect on PTZ-induced kindling seizure behavior, but on the amygdala kindling in rats induced seizure has not been investigated. Objective: In this study, we evaluated the chronic effects of hydro-alcoholic extracts of Anethum graveolens L. on seizures using electrical amygdala kindling model. Methods: Rats were divided into six groups. They were kindled by stimulating the amygdala by consecutive daily. Then, treated by hydro-alcoholic extracts of Anethum graveolens L. ( i.p. 100, 200 and 400 mg/kg) and cumulative After discharge Duration (ADD), Seizure Stage (SS) and Stage 5 seizure (S5D) were recorded. Results: Hydro-alcoholic extracts of Anethum graveolens L. (200 and 400 mg/kg) significantly increased stage 4 Latency compare to the vehicle group (p <0.05 and p<0.01 respectively). Hydro-alcoholic extracts of Anethum graveolens L. (400 mg/kg) injection decreased stage 5 duration compared to vehicle group (p<0.01). Also Hydro-alcoholic extracts of Anethum graveolens L. (100, 200 and 400 mg/kg) injection significantly reduced ADD (p<0.05). Conclusions: According to the obtained results,  the hydro-alcoholic extracts of Anethum graveolens L. has anti-epileptic effect on seizure parameters such as stage 4 Latency, stage 5 duration and ADD.